Original Research: Nurses' Experiences with Racial, Ethnic, Cultural, and Religious Discrimination in the Workplace: A Qualitative Study. Issue 5 (May 2023) - Saadi, Altaf; Taleghani, Sophia; Dillard, Attallah; Ryan, Gery; Heilemann, MarySue; Eisenman, David
ABSTRACT: Background: As the health care workforce diversifies, understanding and addressing the lived experiences of health care professionals facing prejudice and discrimination becomes increasingly important. Previous studies have focused on physicians and medical trainees, but there remains a dearth of research exploring nurses' experiences—even though nurses make up the largest sector of the nation's health care workforce. Objective: This qualitative study explored nurses' experiences of personally mediated workplace discrimination based on race, ethnicity, culture, or religion. Methods: We conducted in-depth interviews with a convenience sample of 15 RNs at one academic medical center. Using an inductive thematic analysis approach, we identified several themes emerging from RNs' experiences and responses to a discriminatory event ("encounter"). Themes were grouped across three phases: pre-encounter, encounter, and post-encounter. Results: Participants reported wide-ranging experiences, from insensitive joking to overt exclusion, coming from various people including patients, patients' family members, colleagues, and physicians. For many, discrimination was cumulative: similar encounters occurred outside the workplace as well as within the clinical setting, often repeatedly, and were influenced by the sociopolitical context. Participants reported a variety of responses, including emotional reactions such as shock, fear of retaliation, and frustration at being expected to represent one's identity group. Silence or inaction predominated bystander and supervisor responses. Although the encounters themselves were fleeting, their impact was enduring. Early-career encounters were most challenging, and participants grappled internally with lasting effects for years. Long-term effects included avoidance of perpetrators, disconnection from colleagues and their own professional role, and leaving the workplace. Conclusions: The findings illuminate nurses' experiences with racial, ethnic, cultural, and religious discrimination in the workplace. Understanding how such discrimination affects nurses is critical to developing effective responses to encounters, creating safer workplaces, and promoting equity within the profession. Abstract : An exploration of how workplace discrimination—from subtle comments to spiteful conduct—can have professional consequences for nurses and may even impact clinical care.